Cross-sectional and longitudinal associations between the built environment and walking: effect modification by socioeconomic status - Chelsea D. Christie; Christine M. Friedenreich; Jennifer E. Vena; Liam Turley; Gavin R. McCormack (BMC, 2022)
Abstract Background Although socioeconomic status (SES) has been shown to modify associations between the neighborhood built environment and physical activity, contradictory results exist. Objectives of this cross-sectional and longitudinal analysis were to: 1) examine whether overall neighborhood walkability and specific built characteristics were associated with walking among adults at a single point in time and after they relocate neighborhoods, and 2) test for effect modification of these associations by SES. Methods We linked longitudinal data from 703 adults who relocated urban neighborhoods between two waves of Alberta's Tomorrow Project (2008-2015) to neighborhood built environment data. We created a walkability index from measures of population counts, street connectivity, and destination diversity within 400 m of participants' homes. In cross-sectional analyses, we used generalized linear models to estimate associations between built characteristics and minutes walked per week at baseline. For the longitudinal analyses, we used fixed-effects linear regression models to estimate associations between changes in built characteristics and minutes walked per week. We also assessed if indicators of SES (individual education or household income) modified both sets of associations. Results Most cross-sectional and longitudinal associations were small and statistically non-significant. Neighborhood population count (b = 0.03, 95% CI: 0.01, 0.07) and street connectivity (b = − 1.75, 95% CI: − 3.26, − 0.24) were cross-sectionally associated with walking duration among the overall sample. None of the longitudinal associations were statistically significant among the overall sample. There was limited evidence of effect modification by SES, however, we found negative cross-sectional associations between street connectivity and walking among adults with lower education and income, and a positive association between percent change in walkability and change in walking among lower educated adults. Conclusions Despite population count and street connectivity being associated with walking at baseline, changes in these built environment variables were not associated with changes in walking following residential relocation. Our findings also provide evidence, albeit weak, that changes in neighborhood walkability, resulting from residential relocation, might more strongly affect walking among low SES adults. Further longitudinal research is needed to examine built environment characteristics with walking for different purposes and to test for inequitable socioeconomic impacts.